An online survey of women's views of respectful and disrespectful pregnancy and early labour care in the Czech Republic - Daly, Deirdre; Begley, Cecily (My University, 2024)
Objective: To ascertain and explore the views of women and their partners, giving birth in the Czech Republic, of the level of respectful or disrespectful care provided during pregnancy and early labour. Design: Ethical approval was granted for a descriptive, online anonymous survey of 65 questions, with quantitative and qualitative responses. Setting: The Czech Republic.The survey was completed by 8,767 women and 69 partners in 2018. Measurements and findings: Descriptive statistics and thematic analysis were used to present results. The majority of women were aged 26-35 years. Most had birthed in one of 93 hospitals, with 1.5% home births. Almost 40% never had an abdominal examination.in pregnancy. Quantitative data analysis revealed that less than half were given information on place of birth, or how to keep labour normal or non-interventionist. Almost 60% did not get information on positions for birth. Most (68%) commenced labour naturally, 25% had labour induced, 40% of them before term, and 7% had an elective caesarean section; 55% stated they had not been given any choice in the decision. Over half of those who had a membrane sweep said permission had not been sought. Half (54%) only had ‘checking’ visits from the midwife in labour. Key conclusions: Findings reveal a lack of information-giving, discussion and shared decision-making from healthcare professionals during pregnancy and early labour. Some practices were non-evidenced-based, and interventions were sometimes made without consent. Implications for practice: The examples of disrespectful care described in this study caused women distress during childbirth, which may result in an increased fear of childbirth or an increase in free-birthing.
PUBLISHED
cited By 0
Keywords: Consent; Decision-making; Maternity care; Respect; Disrespect; Survey